SOSIALISASI PENTINGNYA AIR BERSIH DI PULAU PUSONG LANGSA: UPAYA UNTUK PENINGKATAN KESEJAHTERAAN MASYARAKAT - Mutia, Eka; Purwandito, Meilandy; Novita Lydia, Ellida; Jehan Virgi, Azhemi; Asmarrini; Farhan, Muhammad (Fakultas Teknik, Universitas Samudra, 2023)
challenges regarding access to and understanding the importance of clean water for its community's well-being. In this context, raising awareness about clean water becomes an urgent necessity. This paper aims to summarize and analyze the efforts of socialization carried out on Pusong Island to enhance awareness and access to clean water. The socialization depicts strategies implemented by the PKM Team in introducing the importance of clean water for health and daily life. The results show an increased awareness among the populace regarding the significance of clean water, reflected in behavioral changes regarding water usage and efforts to maintain environmental cleanliness. Additionally, socialization efforts have had a positive impact in reducing the prevalence of diseases caused by contaminated water. Nonetheless, challenges persist, including limited resources and adequate infrastructure. Therefore, recommendations are provided to increase investment in providing broader and sustainable access to clean water, and to strengthen existing socialization programs to reach more people and ensure sustained awareness of the importance of clean water. In conclusion, socialization regarding clean water on Pusong Island has brought significant positive impacts in enhancing awareness and access to this vital resource. However, sustained efforts are necessary to maintain and enhance these achievements to support the future well-being and health of the community on Pusong Island Telaga Tujuh Village Langsa City.